1989
DOI: 10.1038/ki.1989.246
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of impaired natriuretic response to furosemide during prolonged therapy

Abstract: The mechanism of the diuretic braking phenomenon was studied in nine male hypertensive patients by assessing the diurnal pattern of renal sodium (Na) excretion during furosemide therapy, and the response to a test dose of furosemide (10 to 15 mg hr-1 i.v.) infused alone and with chlorothiazide (500 mg bolus i.v.). Patients were studied after one month of twice-daily administration of: placebo (P): chlorothiazide 500 mg (C); furosemide 40 mg (F); furosemide with spironolactone (100 mg b.i.d.) for the last 36 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
121
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 14 publications
1
121
0
5
Order By: Relevance
“…Continuous infusion of furosemide results in a substantial increase in the size of distal cells (43). The same adaptation of distal convoluted tubule has been demonstrated in humans during long-term use of furosemide (96). As a compensatory process, Na ϩ that escapes from the loop of Henle could, therefore, be partially reabsorbed at more distal sites, decreasing overall Increase in distal delivery (C-Li), ml/min Increase in distal delivery (C-Li), ml/min Decrease in GFR (C-In), ml/min Decrease in GFR (C-In), ml/min C D Fig.…”
Section: What Determines the Braking Phenomenon And Is There A Fundammentioning
confidence: 56%
See 1 more Smart Citation
“…Continuous infusion of furosemide results in a substantial increase in the size of distal cells (43). The same adaptation of distal convoluted tubule has been demonstrated in humans during long-term use of furosemide (96). As a compensatory process, Na ϩ that escapes from the loop of Henle could, therefore, be partially reabsorbed at more distal sites, decreasing overall Increase in distal delivery (C-Li), ml/min Increase in distal delivery (C-Li), ml/min Decrease in GFR (C-In), ml/min Decrease in GFR (C-In), ml/min C D Fig.…”
Section: What Determines the Braking Phenomenon And Is There A Fundammentioning
confidence: 56%
“…Although a potential mechanism explaining rebound sodium retention is that furosemide could induce hyperaldosteronism, increases in aldosterone similar after 1 and 3 days of furosemide administration and 4 wk administration furosemide with or without spironolactone had similar effects on sodium balance (96). Moreover, neither ACEi nor ARB treatment could prevent acute diuretic resistance, suggesting that activation of RAAS is not responsible (81,90).…”
Section: What Determines the Braking Phenomenon And Is There A Fundammentioning
confidence: 92%
“…We conclude that there is no significant additive natriuresis with dapagliflozin and bumetanide on first administration. However, there is an adaptive natriuresis over 1 week that is reminiscent of the synergy between loop and thiazide diuretics in subjects adapted to loop diuretics 13, 24. Interestingly, despite rather modest natriuresis, administration of dapagliflozin to patients with T2DM reduced the blood volume, whereas treatment with a thiazide was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…This “diuretic braking phenomenon”14 ultimately leaves many patients with CHF with an expanded blood volume that predicts adverse outcomes 15. Thus, new strategies for treatment of Na + retention are needed 13, 16, 17, 18, 19…”
mentioning
confidence: 99%
“…Studies in rats have shown that chronic administration of a loop diuretic induces hypertrophy and hyperplasia in epithelial cells of the distal convoluted tubule, leading to an increased reabsorption of sodium in this segment, thereby blunting the natriuretic effect. These adaptations also occur in humans 5,6,7 . Management of diuretic resistance (A) Rule out non-compliance Non-compliance with either salt restriction (sodium intake <100 mmol/day) or medication intake should first be excluded.…”
mentioning
confidence: 90%